2008
DOI: 10.29333/ejgm/82601
|View full text |Cite
|
Sign up to set email alerts
|

Hypochromic Microcytic Anemia in Northwestern of Tabriz, Iran

Abstract: Aim: Hypochromic microcytic anemia included iron Deficiency Anemia (IDA) and thalassemia is a worldwide problem with easy treatment and important unwanted symptoms that widely prevalent in Iran.Methods: Present study was undertaken to find prevalence of hypochromic microcytic anemia in Tabriz, Iran. Citizen of Tabriz were taken up for study after they gave a written consent. Subjects were given a questionnaire to elicit anemia related symptoms. Blood counts were done by electronic counter and serum ferritin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…The prevalence of anemia was clearly higher among women totally (OR: 3.17). This is consistent with numerous studies, [ 18 – 20 , 23 , 25 ] and may be simply explained by biological vulnerability of the inevitable iron loss during menstruation and pregnancy in the reproductive age as well as dietary inadequacy. Regarding age, it is important to note that there were differences between the genders.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prevalence of anemia was clearly higher among women totally (OR: 3.17). This is consistent with numerous studies, [ 18 – 20 , 23 , 25 ] and may be simply explained by biological vulnerability of the inevitable iron loss during menstruation and pregnancy in the reproductive age as well as dietary inadequacy. Regarding age, it is important to note that there were differences between the genders.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with the results of the second national integrated micronutrient survey in Iran, which estimated that the anemia prevalence is 10.3% (9.6-11.0%) among adults 45-60 years [18]. In another a population-based cross-sectional study of 1,675 individuals aged 1-90 years in Mashhad, the prevalence of anemia was calculated to be 9.7% [19,20]. Normochromic/microcytic followed by hypochromic/ microcytic and normochromic/normocytic anemias in our study could point towards the fact that malnutrition, iron deficiency, thalassemia and chronic diseases are relevant causes for anemia in Khuzestan population [21].…”
Section: Anemia Status (Prevalence Severity and Subtypes) And Associated Factorssupporting
confidence: 89%
See 1 more Smart Citation
“…There was statistical association between serum ferritin concentration and gender of adults but not with gender of children. This finding is in conformity with the study of Kolahi et al 11 Hypoferritinemia was relatively higher in adult females than the males. This difference could be due to monthly menstrual blood loss women undergo, which invariably causes more hemolysis than erythropoiesis and eventually predispose them to low serum iron store.…”
Section: Discussionsupporting
confidence: 93%
“…The low frequency of hypoferritinemia in these patients was not in consistence with the previous studies which reported higher frequencies of low ferritin levels. [11][12][13] The differences could be due to differences in study location/race, exclusion of undernourished subjects from our study and subject dietary preferences. Most of our patients were not vegetarians coupled with adequate nutritional advice given to them by health professionals in our healthcare center, they were expected to exhibit less cases of IDA.…”
Section: Discussionmentioning
confidence: 99%